2022
DOI: 10.1186/s12884-022-05236-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on physical activity and sedentary behavior during pregnancy: a prospective study

Abstract: Background Prior studies evaluating the impact of the COVID-19 pandemic on pregnancy physical activity (PA) have largely been limited to internet-based surveys not validated for use in pregnancy. Methods This study used data from the Pregnancy PA Questionnaire Validation study conducted from 2019–2021. A prospective cohort of 50 pregnant women completed the Pregnancy PA Questionnaire (PPAQ), validated for use in pregnancy, in early, mid, and late p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Most existing studies have estimated fine dust exposure concentrations based on differences in air quality by region and location [4,11,28,44]. However, as 80-90% of individuals live indoors, owing to COVID-19, the outdoor activity of pregnant women further decreased, and the importance of indoor air quality has been emphasized [45,46]. In this APPO study, indoor PM 2.5 measurements were performed in the residences of pregnant women for at least 1 week, and it is thought that this can give causality to the biological mechanism of any relationship between PM 2.5 and a disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most existing studies have estimated fine dust exposure concentrations based on differences in air quality by region and location [4,11,28,44]. However, as 80-90% of individuals live indoors, owing to COVID-19, the outdoor activity of pregnant women further decreased, and the importance of indoor air quality has been emphasized [45,46]. In this APPO study, indoor PM 2.5 measurements were performed in the residences of pregnant women for at least 1 week, and it is thought that this can give causality to the biological mechanism of any relationship between PM 2.5 and a disease.…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors include heightened psychological distress, such as increased levels of depression and anxiety resulting from fear of the virus and other concerns, which can negatively impact their mental health during the perinatal period[ 42 , 43 ]. Additionally, the implementation of quarantine measures as a response to the pandemic led to prolonged periods of isolation at home[ 44 , 45 ], limiting opportunities for exercise and promoting sedentary lifestyles among pregnant women[ 46 ].…”
Section: Epidemiology Of Gdm During the Pandemicmentioning
confidence: 99%
“…However, after COVID-19, it has become difficult for women to exercise, and there is a significant lack of alternative methods for prenatal management 23 . In accordance with the American College of Obstetrics and Gynecologists (ACOG) recommendation of a minimum of 150 min of exercise per week during pregnancy and postpartum period 24 , Silva-Jose et al suggested that physical activity through virtual modalities could be a suitable alternative, especially in situations where physical activity may be restricted 25 .…”
Section: Introductionmentioning
confidence: 99%